DINAMIKA PASAR MODAL SYARIAH DI INDONESIA: TANTANGAN DAN PELUANG - Laode Muhammad Hasrul Adan; Eny Latifah (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2026)
The purpose of this article is to provide exposure and analysis of the dynamics of the Islamic capital market in Indonesia from the approach of opportunities and challenges that will be faced in the future. The research method uses a qualitative type of literature. The results of the research are the dynamics of the Islamic capital market in Indonesia cannot be separated from the development and see the challenges and opportunities that can be applied for sustainability in the global financial market. The existing opportunities show that there is a need for sustainable ethical awareness; Large Market Potential; Technological Innovation, and Resilience to market turmoil. In addition, it is necessary to know the challenges in the form of uniformity of sharia standards; infrastructure development; volatility; availability and variety of products and the last is literacy and education.